Outcome at 5-6 years of prematurely born children who received morphine as neonates - MacGregor, R. (BMJ Group, 1998)
AIM—To assess outcome at 5-6 years in a cohort of very preterm infants (<34 weeks of gestation) who had been randomly allocated within a controlled clinical trial to receive morphine or non-morphine treatment in the neonatal period. METHODS—Assessments were made on 87 children at 5-6 years who had been recruited in the neonatal period to two sequential controlled studies (1989-92). Infants requiring mechanical ventilation had been randomly allocated to receive either morphine (n=62) or other (n=33) solutions starting on the first day of life. Each child was seen by a single experienced observer and assessed at 5-6 years using the WPPSI-R, Movement ABC, and the Child Behaviour Checklist. The performance of children exposed to morphine was compared with that of those in the non-morphine group. Blood samples for thyroid stimulating hormone (TSH) measurement were obtained from children whose parents gave consent. RESULTS—There was no significant difference in any of the three test scales between infants in the two groups, but there was a trend towards better performance in all three tests in the morphine group. Assessment of TSH values in a subgroup of the survivors showed no difference in thyroid function between the two groups. CONCLUSION—Exposure to morphine in the neonatal period to facilitate mechanical ventilation does not seem to have any adverse effects on intelligence, motor function, or behaviour when these children are assessed at 5-6 years of age.